2017
DOI: 10.22159/ajpcr.2017.v10s2.19482
|View full text |Cite
|
Sign up to set email alerts
|

Significant Drug Interactions Among Intensive Care Unit Patients

Abstract: Objective: Drug interaction is one factor that contributes to drug-related problems. The hospitalized patients in intensive care units (ICU) have a higher risk for developing drug interactions. The purpose of this study was to evaluate the potency of significant drug interactions in ICU patients.Methods: Drug-drug interactions from patient's medical records from ICU of Arifin Achmad General Hospital in Pekanbaru, Province of Riau, Indonesia at period of July to December 2015 were assessed. Drug Interaction Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(21 reference statements)
2
6
0
Order By: Relevance
“…Our study showed a high prevalence of pDDI (81.2%) along with the presence of polypharmacy and the majority of pDDI were clinically relevant (75.08%) which was almost similar to the studies done by Hamidy et al 14 Valizade et al 15 Gupta et al 16 in critically ill patients stressing to the need for increased awareness about the pDDI in health care providers. The reason may be due to the increased number of drugs prescribed per patients with the average number being 7.95±3.07.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study showed a high prevalence of pDDI (81.2%) along with the presence of polypharmacy and the majority of pDDI were clinically relevant (75.08%) which was almost similar to the studies done by Hamidy et al 14 Valizade et al 15 Gupta et al 16 in critically ill patients stressing to the need for increased awareness about the pDDI in health care providers. The reason may be due to the increased number of drugs prescribed per patients with the average number being 7.95±3.07.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was similar to the other studies by Gupta et al Bista et al Bleich et al [16][17][18] Cardiovascular drugs were mainly responsible for clinically relevant drug interaction. Antiplatelet drugs were most commonly involved drugs, mainly Clopidogrel with Aspirin and Clopidogrel with Pantoprazole followed by anti-infective drug Azithromycin with Salbutamol this was in similar to the findings of Baniasadi et al 24 but this was in contrast to the Valizade et al 14 were most commonly involved drugs were Ranitidine followed by Cephalosporin. Variations in patient's presentation, diagnosis, practices and use of medications between ICU settings may lead to different pDDIs patterns.…”
Section: Discussionsupporting
confidence: 81%
“…In our study out of a total of 151 cases collected, 71.5% of cases had the potency of drug-drug interactions. Similarly, other studies reviewed reported a 70% prevalence of potential drug interactions in the ICU patients [8,9]. However, a much higher frequency of drug interactions (91.43%) [10].…”
Section: Discussionmentioning
confidence: 79%
“…In this study it was found that most of the potential drug-drug interactions were of moderate severity (65.9%). Various studies also confirm that most drug interactions identified were of moderate severity [9][10][11].…”
Section: Discussionmentioning
confidence: 79%
“…Among 108 significant drug interactions, dobutamine [55(50.92%)] shows high in frequency due to the complexity of pharmacotherapies administered and ultimately led to adverse effects shown in the study done by Yulis Hamidy. M et al 9 Most of the potential drug interactions were significant (major and moderate) than serious and contraindicated. 10 and Brad E. Cooper.…”
Section: Discussionmentioning
confidence: 99%